Effects of anabolic-androgens on brain reward function - Mhillaj, Emanuela; Morgese, Maria Grazia; Tucci, Paolo; Bove, Maria; Schiavone, Stefania; Trabace, Luigia (Frontiers in Neuroscience, 2015)
Androgens are mainly prescribed to treat several diseases caused by testosterone deficiency. However, athletes try to promote muscle growth by manipulating testosterone levels or assuming androgen anabolic steroids (AAS). These substances were originally synthesized to obtain anabolic effects greater than testosterone. Although AAS are rarely prescribed compared to testosterone, their off-label utilization is very wide. Furthermore, combinations of different steroids and doses generally higher than those used in therapy are common. Symptoms of the chronic use of supra-therapeutic doses of AAS include anxiety, depression, aggression, paranoia, distractibility, confusion, amnesia. Interestingly, some studies have shown that AAS elicited electroencephalographic changes similar to those observed with amphetamine abuse. The frequency of side effects is higher among AAS abusers, with psychiatric complications such as labile mood, lack of impulse control and high violence. On the other hand, AAS addiction studies are complex because data collection is very difficult due to the subjects' reticence and can be biased by many variables, including physical exercise, that alter the reward system. Moreover, it has been reported that AAS may imbalance neurotransmitter systems involved in the reward process, leading to increased sensitivity toward opioid narcotics and central stimulants. The goal of this article is to review the literature on steroid abuse and changes to the reward system in preclinical and clinical studies.